2008
DOI: 10.1128/aem.02719-07
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Folate Production in Fermented Foods by the B 12 Producer Lactobacillus reuteri JCM1112

Abstract: We observed that Lactobacillus reuteri JCM1112 produces B 12 and folate. However, the folate/B 12 mass ratio found was far below that desired for human consumption (ϳ170:1). We used metabolic engineering applying genetic and physiological approaches to improve this ratio and developed a generic and natural process that significantly increases folate production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 24 publications
1
73
0
1
Order By: Relevance
“…Pseudomonas denitrificans and Propionibacterium subspecies account for most of the industrially produced vitamin B 12 , and the productivity is high as 300 mg liter Ϫ1 (8). We have used physiological approaches to modulate the production of B 12 in L. reuteri JCM1112 from nearly undetectable levels to levels 20-fold higher than the levels previously reported (15). Although the level of B 12 produced in this study using L. reuteri falls short of the maximum level reported by nearly 2 orders of magnitude, L. reuteri possesses generally regard as safe status and is a suitable host for in situ production.…”
Section: Discussionmentioning
confidence: 80%
“…Pseudomonas denitrificans and Propionibacterium subspecies account for most of the industrially produced vitamin B 12 , and the productivity is high as 300 mg liter Ϫ1 (8). We have used physiological approaches to modulate the production of B 12 in L. reuteri JCM1112 from nearly undetectable levels to levels 20-fold higher than the levels previously reported (15). Although the level of B 12 produced in this study using L. reuteri falls short of the maximum level reported by nearly 2 orders of magnitude, L. reuteri possesses generally regard as safe status and is a suitable host for in situ production.…”
Section: Discussionmentioning
confidence: 80%
“…Lactobacilli from various fermented foods have been investigated as starter cultures for the manufacturing of folate-fortified dairy products, while lactobacilli isolated from the human gut have been explored as folateproducing probiotics [39][40][41][42]. The availability of genome sequences of various lactobacilli provided an important contribution to the genetics underlying folate biosynthesis in this group of microorganisms [38].…”
Section: Folate Biosynthesis By Human Gut Commensalsmentioning
confidence: 99%
“…This work has been reviewed extensively elsewhere covering the main principles in the field [5][6][7]. Building on these approaches multi-vitamin producing strains have been reported that are able to produce different ratios of folate and cobalamin depending on the food substrate used [8,9].…”
Section: Fermentation In Food Processingmentioning
confidence: 99%
“…In recent years there has been broad array of health modulating metabolites described including anti-inflammatory factors produced by commensals such as Faecalibacterium prausnitzii [53 ] and compounds that can modulate intestinal pain [54]. This also includes essential nutrients such as vitamin K2 important for the modulation of bone mineralisation and blood coagulation [55,56], and vitamin B12 involved in nervous system development [8,57]. The gut microbiota also produces g-aminobutyric acid (GABA), a neurotransmitter involved in the regulation of the central nervous system, relief of hypotension and diuresis [58].…”
Section: Metabolic Products Of the Gut Fermentation Processmentioning
confidence: 99%